2016
DOI: 10.1002/ece3.2553
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community responses to soil tillage and crop rotation in a corn/soybean agroecosystem

Abstract: The acreage planted in corn and soybean crops is vast, and these crops contribute substantially to the world economy. The agricultural practices employed for farming these crops have major effects on ecosystem health at a worldwide scale. The microbial communities living in agricultural soils significantly contribute to nutrient uptake and cycling and can have both positive and negative impacts on the crops growing with them. In this study, we examined the impact of the crop planted and soil tillage on nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(71 citation statements)
references
References 45 publications
5
63
3
Order By: Relevance
“…However, agricultural practices can drive the composition of plant-associated microbiomes to adapt the plant to biotic and abiotic stresses [4]. It has been shown that application of herbicides, pesticides, and tillage practices can lead to shifts in the rhizosphere microbial community compositions [5][6][7][8][9], with possible consequences for crop performance [4,10,11]. In a comparison of plants grown in monocultures and mixtures, it was found that the former had the lowest microbial diversity [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, agricultural practices can drive the composition of plant-associated microbiomes to adapt the plant to biotic and abiotic stresses [4]. It has been shown that application of herbicides, pesticides, and tillage practices can lead to shifts in the rhizosphere microbial community compositions [5][6][7][8][9], with possible consequences for crop performance [4,10,11]. In a comparison of plants grown in monocultures and mixtures, it was found that the former had the lowest microbial diversity [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have indicated that greater asymbiotic N fixation is possible under no-till (Gupta and Roper, 2010; Smith et al, 2016) this is the first study to indicate that greater asymbiotic N is produced in soils under long-term no-till management. This study will hopefully lead to more careful examination of paired fields, or carefully constructed tillage experiments.…”
Section: Discussionmentioning
confidence: 70%
“…Long-term no-till fields generally have a greater supply of C and more diverse C sources compared to a conventional-tilled soil (Awale et al, 2013; Smith et al, 2016). Also, the greater stable aggregation in a no-till soil would provide a habitat for N-fixers and protect them from biocides that they might otherwise encounter (Gupta and Roper, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A majority of studies demonstrate higher soil microbial biomass under notill versus conventional tillage systems (Wardle 1995;D'Hose et al 2018). Soils under reduced or no-till systems also exhibit altered microbial communities in comparison to conventional tillage (Helgason et al 2009;Kuntz et al 2013;Smith et al 2016). These shifts in microbial diversity can change the functional capacity of the communities (Mangalassery et al 2015;Nivelle et al 2016).…”
Section: Tillagementioning
confidence: 99%